A case of co-infection of monkeypox and herpes simplex virus type 1 - E. V. Venev; D. A. Lioznov; A. B. Komissarov; A. V. Fadeev; K. S. Komissarova; N. D. Yolshin; D. A. Gusev (Журнал инфектологии, 2023)
The first Russian clinical case of monkeypox in combination with herpes simplex type 1 infection in a 29-year-old man who returned from Portugal is described. The protocols for sequencing the virus genome are presented. Particular attention is paid to the difficulty of diagnosing vesicular rash in patients with a suspicious history.